The Pyk2/MCU pathway in the rat middle cerebral artery occlusion model of ischemic stroke. (June 2018) - Zhang, Kun; Yan, Jiajia; Wang, Liang; Tian, Xinying; Zhang, Tong; Guo, Li; Li, Bin; Wang, Wang; Liu, Xiaoyun
Highlights: Expression of Pyk2/MCU pathway increased in MCAO model and excitotoxicity model. MCAO and excitotoxicity model present mitochondrial injury and neuronal apoptosis. Inhibition of Pyk2/MCU pathway protects neuron from GLU-induced excitotoxic injury. HUK inhibits Pyk2/MCU pathway and mitigates neuron ischemic and excitotoxic injury. Abstract: Mitochondrial dysfunction caused by Ca 2+ overload plays an important role in ischemia-induced brain damage. Mitochondrial calcium uniporter (MCU), located on the mitochondrial inner membrane, is the major channel responsible for mitochondrial Ca 2+ uptake. Activated proline-rich tyrosine kinase 2 (Pyk2) can directly phosphorylate MCU, which enhances mitochondrial Ca 2+ uptake in cardiomyocytes. It has been suggested that the Pyk2/MCU pathway may be a novel therapeutic target in stress-induced cellular apoptosis. In this study, we explored the role of the Pyk2/MCU pathway in the ischemic brain following a stroke injury. We found that the Pyk2/MCU pathway is activated in a rat cerebral ischemia model, and is responsible for mitochondrial dysfunction and neuronal apoptosis. Inhibiting the Pyk2/MCU pathway with a Pyk2 inhibitor (PF-431396) prevented mitochondrial Ca 2+ overload, mitochondrial injury, proapoptotic protein release, and cell death. Interestingly, human urinary kallidinogenase (HUK) alleviated neuronal ischemic injury by inhibiting the Pyk2/MCU pathway, suggesting that the Pyk2/MCU pathway may be a protective target for ischemic stroke treatment.